Nurses' perceptions of the reliability of an automated medication dispensing system. - Novek J; Bettess S; Burke K; Johnston P (Journal of Nursing Care Quality, 2000)
Automated medication dispensing systems (AMDS) technology is increasingly being implemented in health care facilities to reduce the risk of medication errors. However, the case study evidence of their effectiveness has so far been mixed. It has been suggested that the attitudes of nursing staff toward AMDS can be an important factor in influencing whether or not the technology will be successfully implemented. Nurses' attitudes toward AMDS were examined at Riverview Health Centre, a long-term care facility where the Meditrol automated dispensing system had been installed the previous year. It was found that nurses were generally distrustful of AMDS and skeptical that it had reduced medication errors. A number of technological, organizational, and social factors has been put forward to explain this distrust. In addition, the efforts of hospital administrators to raise nurses' confidence in the system's reliability were also delineated. Copyright © 2000 by Aspen Publishers, Inc.